The Modification of the Social and Gnoseological Nature of Religion - Minkevičius, Jokūbas (Problemos, 1974)
In its social and epistemological nature religion is a kind of reflexion of human knowledge and praxis, when individuals are always in certain social relations which determine the fate of religion itself. Modem scientific and technological progress is accompanied not only by a decline of religion, but there are some contrary factors too. While there are contradictions and negative consequences of modern revolution in science and technology, in which arise many complicated and difficult problems of social control, there is a remarkable modification in the contents of religious consciousness and theology towards a new presentation of human situation in modern context “Man – Science – Technology”. Christian or similar humanisms confront their spiritual values as an alternative to the rationalist technocratic orientation in modern “Society of consumption”. Ethical and axiological antinomies of contemporary bourgeois culture and industrial civilization, disintegration of bourgeois philosophy make convenient conditions for religion and theology to discredit the progress of science and technology both in the spheres of methodology and sociology. In a socialist society, where various forms of alienation may be overcome, the social roots of religion may disappear.